Protective effect of natural products in the metabolic-associated kidney diseases via regulating mitochondrial dysfunction - Liu, Peng; Chen, Yao; Xiao, Jing; Zhu, Wenhui; Yan, Xiaoming; Chen, Ming (Frontiers in Pharmacology, 2023)
Metabolic syndrome (MS) is a complex group of metabolic disorders syndrome with hypertension, hyperuricemia and disorders of glucose or lipid metabolism. As an important organ involved in metabolism, the kidney is inevitably attacked by various metabolic disorders, leading to abnormalities in kidney structure and function. Recently, an increasing number of studies have shown that mitochondrial dysfunction is actively involved in the development of metabolic-associated kidney diseases. Mitochondrial dysfunction can be used as a potential therapeutic strategy for the treatment of metabolic-associated kidney diseases. Many natural products have been widely used to improve the treatment of metabolic-associated kidney diseases by inhibiting mitochondrial dysfunction. In this paper, by searching several authoritative databases such as PubMed, Web of Science, Wiley Online Library, and Springer Link. we summarize the Natural Products Protect Against Metabolic-Associated Kidney Diseases by Regulating Mitochondrial Dysfunction. In this review, we sought to provide an overview of the mechanisms by which mitochondrial dysfunction impaired metabolic-associated kidney diseases, with particular attention to the role of mitochondrial dysfunction in diabetic nephropathy, gouty nephropathy, hypertensive kidney disease, and obesity-related nephropathy, and then the protective role of natural products in the kidney through inhibition of mitochondrial disorders, thus providing a systematic understanding of the targets of mitochondrial dysfunction in metabolic-associated kidney diseases, and finally a review of promising therapeutic targets and herbal candidates for metabolic-associated kidney diseases through inhibition of mitochondrial dysfunction.